PENGARUH SOLVABILITAS (DEBT EQUITY RATIO), PROFITABILITAS(RETURN ON EQUITY), DAN CURRENT RATIO TERHADAP RETURN SAHAM - Yeni Ariesa; Agnes Reslita (JEBIM Prima, 2020)
The objective of the study is to examine the effect of debt equity ratio, return on equity, and current ratio on stock returns. The independent variable is stock returns while the dependent variables are debt equity ratio, return on equity and current ratio. The research used a quantitative research approach, while the type of the study was descriptive statistics, and the nature of the study was an explanatory study. The research populations were 39 companies in the consumer goods industry sector while the 18 samples were drawn by using a purposive sampling technique consisting of consumer goods industries that met the criteria. The research data were analyzed by using multiple linear regression analysis with the classical assumption test. Simultaneously, the research revealed that the debt equity ratio, return on equity and current ratio did not affect stock returns in the consumer goods industry sector listed on the Indonesia Stock Exchange in the period of 2014-2018. The calculation points out that F-count <F-table or 0.412 <2.92 with a significant level of 0.745> 0.05. Partially, the debt equity ratio, return on equity, and current ratio did not have any significant effect on stock returns in the Consumer Goods Industry sector companies listed on the Indonesia Stock Exchange in the period of 2014-2018